Present status of haploidy research in onion (Allium cepa) – A review - KHAR, ANIL; ISLAM, SABINA; KALIA, PRITAM; BHATIA, REETA; KUMAR, ARUN (The Indian Journal of Agricultural Sciences, 2019)
Research on haploid induction and their subsequent utilization in basic and genomic research and breeding is still at its infancy due to paucity of research efforts, difficulties in various critical steps, large genome size and limited publications. Haploid development in onion (Allium cepa L.) is only feasible through in-vitro gynogenesis and is influenced by genotype, geographic origin, genetic constitution, physiological stage, growth conditions and cultural conditions. Pollination with irradiated pollen has been reported to induce haploids in onion. However, more successful methodology is through whole flower bud culture. After haploid induction, chromosome doubling, for doubled haploids (DHs) induction, is another limiting factor. Whole basal plant as an explant and amiprofos-methyl as a chromosome doubling agent has been found to be safe and effective. Potential of DH lines has been explored through the study of hybrids using DH as parents and hybrids have been found uniform and promising compared to conventionally developed hybrids. DH line 'Onion haploid OH-1' has been released by USDA to serve as a responsive control for the extraction of gynogenic haploids. DH's have been successfully utilized in onion genomic research for identification of gene and genomic regions affecting quality traits like colour, restorer of male sterility (Ms) locus, bolting, fructan etc. Future studies need to focus on identification of haploidy inducing gene/QTLs, gynogenic responsive genes, establishment of efficient chromosome doubling techniques, restoration of fecundity of DH genotypes and methodology standardisation to transfer them in less/non-responsive desirable genotypes.